Flattening the Curve, Constitutional Crisis and Immigrants' Rights Protections: The Case of Israel - Kritzman-Amir, Tally (Frontiers in Political Science, 2021)
Despite being a small and relatively secluded country, managing the COVID-19 pandemic has so far been quite a challenge for Israel. This contribution seeks to explain how Israel had managed migration and the pandemic amidst a constitutional crisis between February and July 2020.